Bismuth ferrite-barium titanate piezoelectric ceramic with heterostructure and preparation method thereof
By forming heterostructure and adding MnO2 on the surface of BiFeO3-BaTiO3 ceramics, the problem of sacrificing thermal stability when improving piezoelectric properties is solved, and the improvement of high-temperature piezoelectric properties and the maintenance of thermal stability is achieved. .
Patent Information
- Application Number
- CN202411551338.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-11-01
AI Technical Summary
Existing lead-free piezoelectric ceramics sacrifice thermal stability while improving piezoelectric properties, limiting their use in high-temperature applications.
Through ABA stacked structure and ion diffusion technology, heterostructure is formed on the surface of BiFeO3-BaTiO3 ceramics, improving the ion disorder of Bi(Ba) and Fe position and relaxing ferroelectric characteristics, enhancing the piezoelectric performance, and optimizing through the addition of MnO2 Depolarization temperature of ceramics.
The high-temperature piezoelectric performance was improved, and the piezoelectric coefficient d33>120pC/N and the depolarization temperature Td>400℃ were obtained, while the use of lead and precious metals was avoided.
Smart Images

Figure CN119390439A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of piezoelectric ceramics, and in particular to a bismuth ferrite-barium titanate piezoelectric ceramic with a heterogeneous structure and a preparation method thereof. Background Art
[0002] Piezoelectric ceramics have the characteristics of mutual conversion between electrical energy and mechanical energy, and are widely used in weapons industry, aerospace, security alarm, medical equipment, household appliances, oil exploration, etc. At present, Pb-based piezoelectric ceramics represented by lead zirconate titanate (PZT) have excellent piezoelectric properties (d 33 ≥300pC / N) and high Curie temperature (Tc≥300℃) occupy the main commercial market. With the increasing awareness of the impact of lead on human health and environmental protection, the use of lead has been restricted by law, which has prompted people to find and develop lead-free piezoelectric ceramics as an effective substitute for PZT. Therefore, it is urgent to seek new high-temperature lead-free piezoelectric ceramics.
[0003] The current hot lead-free piezoelectric ceramics include (Bi 0.5 Na 0.5 )TiO3(T C ≈320℃)、BiFeO3-BaTiO3(T C ≈454℃)、(K 0.5 Na 0.5 )NbO3(T C ≈420℃)、BaTiO3(T C ≈115℃). BiFeO3-BaTiO3 based ceramics have a high Curie temperature T C ≈454℃ and has attracted much attention, but its low piezoelectric performance d 33 ≤120pC / N limits its application, which is generally controlled by traditional ion doping, introduction of third elements, process optimization and other methods. The literature (S. Guan, H. Yang, G. Qiao, et al., Journal of Electronic Materials, 2020.49(10): p.6199-6207) obtained the piezoelectric constant d by adding Li2CO3 and CuO to 0.7BF-0.3BT lead-free piezoelectric ceramics. 33 =168pC / N, but the piezoelectric performance is enhanced at the expense of thermal stability, which is not conducive to the high-temperature application of BiFeO3-BaTiO3-based ceramics. Summary of the invention
[0004] The invention provides a bismuth ferrite-barium titanate piezoelectric ceramic with a heterogeneous structure and good piezoelectric performance and thermal stability, and a preparation method thereof.
[0005] The technical solution provided by the present invention is a bismuth ferrite-barium titanate piezoelectric ceramic with a heterogeneous structure, and the ceramic is formed by sequentially stacking and pressing an A layer material, a B layer material and an A layer material;
[0006] The general structural formula of the A layer material is: BaTi (1-x) Sn x O3;
[0007] The structural formula of the B layer material is: 0.75BiFeO3-0.25BaTiO3-ywt%MnO2;
[0008] Wherein x represents the molar fraction, 0<x≤0.16; y=MnO2 weight / B layer material total weight×100, and 0<y≤1.
[0009] Preferably, the weight ratio of the A layer material, the B layer material and the A layer material is 1:2.5:1.
[0010] Preferably, 0.07≤x≤0.16, 0.1≤y≤0.7.
[0011] More preferably, x=0.07, y=0.1.
[0012] The present invention also provides a method for preparing a bismuth ferrite-barium titanate piezoelectric ceramic having a heterogeneous structure, comprising the following steps:
[0013] 1) Using SnO2, BaCO3, and TiO2 as raw materials according to BaTi (1-x) Sn x O3 chemical formula is used for mixing, anhydrous ethanol is used as a solvent for grinding, and after being taken out, it is dried and fired at 1150℃~1200℃ for 3~6h to obtain the A layer material;
[0014] 2) Bi2O3, Fe2O3, BaCO3 and TiO2 are used as raw materials and prepared according to the chemical formula of 0.75BiFeO3-0.25BaTiO3, ground with anhydrous ethanol as solvent, taken out and dried, and fired at 750°C to 850°C for 2 to 4 hours to obtain 0.75BiFeO3-0.25BaTiO3 powder;
[0015] 3) Add MnO2 to the 0.75BiFeO3-0.25BaTiO3 powder of step 2) according to the chemical formula of 0.75BiFeO3-0.25BaTiO3-ywt%MnO2, grind with anhydrous ethanol as solvent, take out and dry, and obtain the B layer material;
[0016] 4) After ball-milling the A layer material and the B layer material respectively, adding an appropriate amount of PVA to obtain the A layer raw material and the B layer raw material, and stacking the A layer raw material and the B layer raw material in the order of A, B, A, and pressing them into sheets to obtain a plain sheet;
[0017] 5) The plain sheet is heated to 600°C and kept at this temperature for 1 to 3 hours to remove binder, then heated to 950 to 1000°C and kept at this temperature for 4 to 6 hours, cooled to room temperature, silver-brushed on both sides, fired, and polarized in silicone oil to obtain a piezoelectric ceramic.
[0018] In step 4), the amount of PVA added to the A layer material is 10-15% of the weight of the A layer material; the amount of PVA added to the B layer material is 10-15% of the weight of the B layer material.
[0019] In step 5), the temperature of the silver-brushed plain sheet is slowly increased to 600° C. at a heating rate of 5° C. / min and kept at this temperature for 2 h.
[0020] In step 5), the polarization electric field is 4000-5000 V / mm, the temperature is 80-100° C., and the time is 15-20 min.
[0021] The present invention has the following beneficial effects:
[0022] 1) The present invention forms a heterogeneous structure on the surface of BiFeO3-BaTiO3 ceramics through an ABA stacked structure (BST-BFBT-BST) by ion diffusion technology, thereby improving the disorder degree and relaxor ferroelectric properties of Bi(Ba) and Fe ions in the system and enhancing the depolarization temperature of the system.
[0023] 2) Use ion diffusion technology to refine the ferroelectric domains on the surface of BiFeO3-BaTiO3 ceramics, reduce the domain inversion barrier, and improve the piezoelectric properties of the system.
[0024] 3) The ceramics prepared by the present invention have excellent high-temperature piezoelectric properties and obtain a large piezoelectric coefficient d 33 >120pC / N and depolarization temperature T d >400℃, and does not contain toxic elements Pb and precious metals Sc, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 The dielectric temperature spectrum curve of the piezoelectric ceramic of Example 1 of the present invention;
[0026] Figure 2 This is an in-situ dynamic depolarization curve diagram of the piezoelectric ceramic of Example 1 of the present invention. DETAILED DESCRIPTION
[0027] The present invention will be further described below with reference to examples, but the present invention is not limited to these examples.
[0028] Example 1
[0029] The general structural formula of the A layer material is: BaTi 0.93 Sn 0.07 O3;
[0030] The general structural formula of the B layer material is: 0.75BiFeO3-0.25BaTiO3-0.1wt%MnO2;
[0031] Preparation method:
[0032] 1) Preparation of A layer material:
[0033] Using analytical pure SnO2, BaCO3, and TiO2 as raw materials, according to BaTi 0.93 Sn 0.07 O3 is used for mixing, zirconium balls are used as grinding media, anhydrous ethanol is used as solvent, ball milling is performed for 12 hours, and after being taken out, it is dried at 80°C for 4 hours, and then pre-calcined at 1150°C for 3 hours to obtain the A layer material.
[0034] 2) Preparation of B layer material:
[0035] Analytical pure Bi2O3, Fe2O3, BaCO3, TiO2 were used as raw materials and the chemical formula of 0.75BiFeO3-0.25BaTiO3 was used. Zirconium balls were used as grinding media and anhydrous ethanol was used as solvent. The mixture was ball milled for 12 hours, dried at 80℃ for 4 hours, and then pre-calcined at 750℃ for 2 hours to obtain
[0036] 0.75BiFeO3-0.25BaTiO3 powder;
[0037] Analytical pure MnO2 was added to 0.75BiFeO3-0.25BaTiO3 powder, the weight of MnO2 added was 0.1% of the total weight of the mixed powder, zirconium balls were used as grinding media, anhydrous ethanol was used as solvent, ball milling was performed for 12 hours, and after taking out, it was dried at 80°C for 4 hours to obtain B layer material.
[0038] 3) Pour the A layer material into a mortar, grind it and add 10% PVA by weight of the A layer material to obtain the A layer raw material.
[0039] 4) Pour the B layer material into a mortar, grind it and add 10% PVA by weight of the B layer material to obtain the B layer raw material.
[0040] 5) The A layer raw material and the B layer raw material are stacked and pressed into tablets in the order of A, B, and A. The weights of the three layers of raw materials are 0.1 g, 0.25 g, and 0.1 g, respectively, to obtain plain tablets with a diameter of 10 mm.
[0041] 6) Debinding: slowly heat the plain sheet to 600°C at a heating rate of 5°C / min, keep it warm for 1 hour to debind, then heat it to 950°C and keep it warm for 4 hours, cool it to room temperature with the furnace, and process it into a thin sheet with smooth two sides and a thickness of 0.5 mm.
[0042] 7) Silver plating: In order to facilitate the subsequent electrical performance test, the thin film was silver-plated, that is, silver was brushed on both sides of the thin film by screen printing, and the diameter of the conductive silver surface was 8 mm. It was then placed in a muffle furnace and kept at 700°C for 0.5h to obtain a silver-plated thin film.
[0043] 8) Polarization: The silver-plated sheet was polarized in silicone oil at a polarization electric field of 4000 V / mm, a temperature of 80° C., and a time of 15 min. The electric field was maintained and the sheet was cooled to room temperature.
[0044] The performance test results are as follows:
[0045] <![CDATA[d 33 (pC / N)]]> <![CDATA[Q m ]]> <![CDATA[k p ]]> <![CDATA[ε r ]]> Tanδ(%) <![CDATA[T C (℃)]]> <![CDATA[T d (℃)]]> 169 81.652 295.61 405 3.54 563 404
[0046] Comparative Example 1
[0047] The general structural formula of the B layer material is: 0.75BiFeO3-0.25BaTiO3-0.1wt%MnO2;
[0048] 1) Preparation of layer B material: the same as step 2) of Example 1;
[0049] 2) Pour the B layer material into a mortar, grind it and add PVA which is 10% of the weight of the B layer material to obtain the B layer raw material. Take 0.45 g of the B layer raw material and press it into a sheet to obtain a plain sheet with a diameter of 10 mm.
[0050] 3) The plain sheet is subjected to debinding, silver plating and polarization treatment to obtain a piezoelectric ceramic. This step is the same as steps 6), 7) and 8) of Example 1.
[0051] The performance test results are as follows:
[0052] <![CDATA[d 33 (pC / N)]]> <![CDATA[Q m ]]> <![CDATA[k p ]]> <![CDATA[ε r ]]> Tanδ(%) <![CDATA[T C (℃)]]> <![CDATA[T d (℃)]]> 104 76.352 265.61 385 2.74 575 300
[0053] Example 2
[0054] The general structural formula of the A layer material is: BaTi 0.91 Sn 0.09 O3;
[0055] The general structural formula of the B layer material is: 0.75BiFeO3-0.25BaTiO3-0.3wt%MnO2;
[0056] Preparation method:
[0057] 1) Preparation of A layer material:
[0058] Using analytical pure SnO2, BaCO3, and TiO2 as raw materials, according to BaTi 0.91 Sn 0.09 O3 is used for mixing, zirconium balls are used as grinding media, anhydrous ethanol is used as solvent, ball milling is performed for 15 hours, and after being taken out, it is dried at 80°C for 4 hours, and then pre-calcined at 1200°C for 6 hours to obtain the A layer material.
[0059] 2) Preparation of B layer material:
[0060] Analytical pure Bi2O3, Fe2O3, BaCO3, TiO2 were used as raw materials and the chemical formula of 0.75BiFeO3-0.25BaTiO3 was used. Zirconium balls were used as grinding media and anhydrous ethanol was used as solvent. The mixture was ball milled for 15 hours, dried at 80°C for 4 hours, and then pre-calcined at 850°C for 4 hours to obtain
[0061] 0.75BiFeO3-0.25BaTiO3 powder;
[0062] Analytical pure MnO2 was added to 0.75BiFeO3-0.25BaTiO3 powder, the amount of MnO2 added was 0.3% of the total weight of the mixed powder, zirconium balls were used as grinding media, anhydrous ethanol was used as solvent, ball milling was performed for 15 hours, and after taking out, it was dried at 80°C for 4 hours to obtain the B layer material.
[0063] 3) Pour the A layer material into a mortar, grind it and add 15% PVA by weight of the A layer material to obtain the A layer raw material.
[0064] 4) Pour the B layer material into a mortar, grind it and add 15% PVA of the weight of the B layer material to obtain the B layer raw material.
[0065] 5) The A layer raw material and the B layer raw material are stacked and pressed into tablets in the order of A, B, and A. The weights of the three layers of raw materials are 0.1 g, 0.25 g, and 0.1 g, respectively, to obtain plain tablets with a diameter of 10 mm.
[0066] 6) Debinding: slowly heat the plain sheet to 600°C at a heating rate of 5°C / min, keep it warm for 3 hours to debind, then heat it to 1000°C and keep it warm for 6 hours, cool it to room temperature with the furnace, and process it into a thin sheet with smooth two sides and a thickness of 0.5 mm.
[0067] 7) Silver plating: In order to facilitate the subsequent electrical performance test, the thin film was silver-plated, that is, silver was brushed on both sides of the thin film by screen printing, and the diameter of the conductive silver surface was 8 mm. It was then placed in a muffle furnace and kept at 700°C for 0.5h to obtain a silver-plated thin film.
[0068] 8) Polarization: The silver-plated sheet was polarized in silicone oil with a polarization electric field of 5000 V / mm, a temperature of 100° C., and a time of 20 min. The electric field was maintained and the sheet was cooled to room temperature.
[0069] The performance test results are as follows:
[0070] <![CDATA[d 33 (pC / N)]]> <![CDATA[Q m ]]> <![CDATA[k p ]]> <![CDATA[ε r ]]> Tanδ(%) <![CDATA[T C (℃)]]> <![CDATA[T d (℃)]]> 130 75.694 202.81 410 3.75 558 390
[0071] Comparative Example 2
[0072] The general structural formula of the B layer material is: 0.75BiFeO3-0.25BaTiO3-0.3wt%MnO2;
[0073] 1) Preparation of layer B material: the same as step 2) in Example 2;
[0074] 2) Pour the B layer material into a mortar, grind it and add PVA which is 15% of the weight of the B layer material to obtain the B layer raw material. Take 0.45 g of the B layer raw material and press it into a sheet to obtain a plain sheet with a diameter of 10 mm.
[0075] 3) The plain sheet is subjected to debinding, silver plating and polarization treatment to obtain a piezoelectric ceramic. This step is the same as steps 6), 7) and 8) of Example 2.
[0076] The performance test results are as follows:
[0077] <![CDATA[d 33 (pC / N)]]> <![CDATA[Q m ]]> <![CDATA[k p ]]> <![CDATA[ε r ]]> Tanδ(%) <![CDATA[T C (℃)]]> <![CDATA[T d (℃)]]> 102 71.694 200.67 388 2.98 560 381
[0078] Example 3
[0079] The general structural formula of the A layer material is: BaTi 0.89 Sn 0.11 O3;
[0080] The general structural formula of the B layer material is: 0.75BiFeO3-0.25BaTiO3-0.5wt%MnO2;
[0081] Preparation method:
[0082] 1) Preparation of A layer material:
[0083] Using analytical pure SnO2, BaCO3, and TiO2 as raw materials, according to BaTi 0.89 Sn 0.11 O3 is used for mixing, zirconium balls are used as grinding media, anhydrous ethanol is used as solvent, ball milling is performed for 14 hours, and after being taken out, it is dried at 80°C for 4 hours, and then pre-calcined at 1180°C for 4 hours to obtain the A layer material.
[0084] 2) Preparation of B layer material:
[0085] Analytical pure Bi2O3, Fe2O3, BaCO3, TiO2 were used as raw materials and the chemical formula of 0.75BiFeO3-0.25BaTiO3 was used. Zirconium balls were used as grinding media and anhydrous ethanol was used as solvent. The mixture was ball milled for 14 hours, dried at 80°C for 4 hours, and then pre-calcined at 800°C for 3 hours to obtain
[0086] 0.75BiFeO3-0.25BaTiO3 powder;
[0087] Analytical pure MnO2 was added to 0.75BiFeO3-0.25BaTiO3 powder, the weight of MnO2 added was 0.5% of the total weight of the mixed powder, zirconium balls were used as grinding media, anhydrous ethanol was used as solvent, ball milling was performed for 14 hours, and after taking out, it was dried at 80°C for 4 hours to obtain B layer material.
[0088] 3) Pour the A layer material into a mortar, grind it and add 12% PVA by weight of the A layer material to obtain the A layer raw material.
[0089] 4) Pour the B layer material into a mortar, grind it and add 12% PVA by weight of the B layer material to obtain a B layer raw material.
[0090] 5) The A layer raw material and the B layer raw material are stacked and pressed into tablets in the order of A, B, and A. The weights of the three layers of raw materials are 0.1 g, 0.25 g, and 0.1 g, respectively, to obtain plain tablets with a diameter of 10 mm.
[0091] 6) Debinding: slowly heat the plain sheet to 600°C at a heating rate of 5°C / min, keep it warm for 2 hours to debind, then heat it to 980°C and keep it warm for 5 hours, cool it to room temperature with the furnace, and process it into a thin sheet with smooth two sides and a thickness of 0.5 mm.
[0092] 7) Silver plating: In order to facilitate the subsequent electrical performance test, the thin film was silver-plated, that is, silver was brushed on both sides of the thin film by screen printing, and the diameter of the conductive silver surface was 8 mm. It was then placed in a muffle furnace and kept at 700°C for 0.5h to obtain a silver-plated thin film.
[0093] 8) Polarization: The silver-plated sheet was polarized in silicone oil at a polarization electric field of 4500 V / mm, a temperature of 90° C., and a time of 18 min. The electric field was maintained and the sheet was cooled to room temperature.
[0094] The performance test results are as follows:
[0095] <![CDATA[d 33 (pC / N)]]> <![CDATA[Q m ]]> <![CDATA[k p ]]> <![CDATA[ε r ]]> Tanδ(%) <![CDATA[T C (℃)]]> <![CDATA[T d (℃)]]> 135 61.664 242.17 484 4.32 565 387
[0096] Comparative Example 3
[0097] The general structural formula of the B layer material is: 0.75BiFeO3-0.25BaTiO3-0.5wt%MnO2;
[0098] 1) Preparation of layer B material: the same as step 2) in Example 3;
[0099] 2) Pour the B layer material into a mortar, grind it and add PVA which is 12% of the weight of the B layer material to obtain the B layer raw material. Take 0.45 g of the B layer raw material and press it into a sheet to obtain a plain sheet with a diameter of 10 mm.
[0100] 3) The plain sheet is subjected to debinding, silver plating and polarization treatment to obtain a piezoelectric ceramic. This step is the same as steps 6), 7) and 8) of Example 3.
[0101] The performance test results are as follows:
[0102] <![CDATA[d 33 (pC / N)]]> <![CDATA[Q m ]]> <![CDATA[k p ]]> <![CDATA[ε r ]]> Tanδ(%) <![CDATA[T C (℃)]]> <![CDATA[T d (℃)]]> 106 58.023 243.84 450 3.89 567 374
[0103] Example 4
[0104] The general structural formula of the A layer material is: BaTi 0.84 Sn 0.16 O3;
[0105] The general structural formula of the B layer material is: 0.75BiFeO3-0.25BaTiO3-0.7wt%MnO2;
[0106] Preparation method:
[0107] 1) Preparation of A layer material:
[0108] Using analytical pure SnO2, BaCO3, and TiO2 as raw materials, according to BaTi 0.84 Sn 0.16 O3 is used for mixing, zirconium balls are used as grinding media, anhydrous ethanol is used as solvent, ball milling is performed for 12 hours, and after being taken out, it is dried at 80°C for 4 hours, and then pre-calcined at 1200°C for 3 hours to obtain the A layer material.
[0109] 2) Preparation of B layer material:
[0110] Analytical pure Bi2O3, Fe2O3, BaCO3, TiO2 were used as raw materials and the chemical formula of 0.75BiFeO3-0.25BaTiO3 was used. Zirconium balls were used as grinding media and anhydrous ethanol was used as solvent. The mixture was ball milled for 15 hours, dried at 80°C for 4 hours, and then pre-calcined at 750°C for 4 hours to obtain
[0111] 0.75BiFeO3-0.25BaTiO3 powder;
[0112] Analytical pure MnO2 was added to 0.75BiFeO3-0.25BaTiO3 powder, the weight of MnO2 added was 0.7% of the total weight of the mixed powder, zirconium balls were used as grinding media, anhydrous ethanol was used as solvent, ball milling was performed for 12 hours, and after taking out, it was dried at 80°C for 4 hours to obtain B layer material.
[0113] 3) Pour the A layer material into a mortar, grind it and add 12.5% PVA by weight of the A layer material to obtain the A layer raw material.
[0114] 4) Pour the B layer material into a mortar, grind it, and add 12.5% PVA by weight of the B layer material to obtain a B layer raw material.
[0115] 5) The A layer raw material and the B layer raw material are stacked and pressed into tablets in the order of A, B, and A. The weights of the three layers of raw materials are 0.1 g, 0.25 g, and 0.1 g, respectively, to obtain plain tablets with a diameter of 10 mm.
[0116] 6) Debinding: slowly heat the plain sheet to 600°C at a heating rate of 5°C / min, keep it warm for 2 hours to debind, then heat it to 1000°C and keep it warm for 4 hours, cool it to room temperature with the furnace, and process it into a thin sheet with smooth two sides and a thickness of 0.5 mm.
[0117] 7) Silver plating: In order to facilitate the subsequent electrical performance test, the thin film was silver-plated, that is, silver was brushed on both sides of the thin film by screen printing, and the diameter of the conductive silver surface was 8 mm. It was then placed in a muffle furnace and kept at 700°C for 0.5h to obtain a silver-plated thin film.
[0118] 8) Polarization: The silver-plated sheet was polarized in silicone oil with a polarization electric field of 4000 V / mm, a temperature of 100° C., and a time of 15 min. The electric field was maintained and the sheet was cooled to room temperature.
[0119] The performance test results are as follows:
[0120] <![CDATA[d 33 (pC / N)]]> <![CDATA[Q m ]]> <![CDATA[k p ]]> <![CDATA[ε r ]]> Tanδ(%) <![CDATA[T C (℃)]]> <![CDATA[T d (℃)]]> 137 51.743 306.49 435 4.69 573 350
[0121] Comparative Example 4
[0122] The general structural formula of the B layer material is: 0.75BiFeO3-0.25BaTiO3-0.7wt%MnO2;
[0123] 1) Preparation of layer B material: the same as step 2) in Example 3;
[0124] 2) Pour the B layer material into a mortar, grind it and add PVA in an amount of 12.5% by weight of the B layer material to obtain the B layer raw material. Take 0.45 g of the B layer raw material and press it into a sheet to obtain a plain sheet with a diameter of 10 mm.
[0125] 3) The plain sheet is subjected to debinding, silver plating and polarization treatment to obtain a piezoelectric ceramic. This step is the same as steps 6), 7) and 8) of Example 3.
[0126] The performance test results are as follows:
[0127] <![CDATA[d 33 (pC / N)]]> <![CDATA[Q m ]]> <![CDATA[k p ]]> <![CDATA[ε r ]]> Tanδ(%) <![CDATA[T C (℃)]]> <![CDATA[T d (℃)]]> 98 50.875 301.66 422 3.29 560 300
Claims
1. A bismuth ferrite-barium titanate piezoelectric ceramic with a heterostructure, characterized in that: The ceramic is formed by sequentially stacking and pressing an A-layer material, a B-layer material and an A-layer material; The general structural formula of the A layer material is: BaTi (1-x) Sn x O3; The general structural formula of the B layer material is: 0.75BiFeO3-0.25BaTiO3-ywt%MnO2; Wherein x represents the molar fraction, 0<x≤0.16; y=MnO2 weight / B layer material total weight×100, and 0<y≤1.
2. The bismuth ferrite-barium titanate piezoelectric ceramic with a heterostructure according to claim 1, characterized in that: The weight ratio of the A layer material, the B layer material and the A layer material is 1:2.5:
1.
3. The bismuth ferrite-barium titanate piezoelectric ceramic with a heterostructure according to claim 1, characterized in that: 0.07≤x≤0.16, 0.1≤y≤0.
7.
4. The bismuth ferrite-barium titanate piezoelectric ceramic with a heterostructure according to claim 3, characterized in that: x=0.07, y=0.
1.
5. The method for preparing the bismuth ferrite-barium titanate piezoelectric ceramic with a heterostructure according to any one of claims 1 to 4, characterized in that: The following steps are involved: 1) Using SnO2, BaCO3, and TiO2 as raw materials according to BaTi (1-x) Sn x O3 chemical formula is used for mixing, anhydrous ethanol is used as a solvent for grinding, and after being taken out, it is dried and fired at 1150℃~1200℃ for 3~6h to obtain the A layer material; 2) Bi2O3, Fe2O3, BaCO3 and TiO2 are used as raw materials and prepared according to the chemical formula of 0.75BiFeO3-0.25BaTiO3, ground with anhydrous ethanol as solvent, taken out and dried, and fired at 750°C to 850°C for 2 to 4 hours to obtain 0.75BiFeO3-0.25BaTiO3 powder; 3) Add MnO2 to the 0.75BiFeO3-0.25BaTiO3 powder of step 2) according to the chemical formula of 0.75BiFeO3-0.25BaTiO3-ywt%MnO2, grind with anhydrous ethanol as solvent, take out and dry, and obtain the B layer material; 4) After ball-milling the A layer material and the B layer material respectively, adding an appropriate amount of PVA to obtain the A layer raw material and the B layer raw material, and stacking the A layer raw material and the B layer raw material in the order of A, B, A, and pressing them into sheets to obtain a plain sheet; 5) The plain sheet is heated to 600°C and kept at this temperature for 1 to 3 hours to remove binder, then heated to 950 to 1000°C and kept at this temperature for 4 to 6 hours, cooled to room temperature, silver-brushed on both sides, fired, and polarized in silicone oil to obtain a piezoelectric ceramic.
6. The method for preparing the bismuth ferrite-barium titanate piezoelectric ceramic with a heterostructure according to claim 5, characterized in that: In step 4), the amount of PVA added to the A layer material is 10-15% of the weight of the A layer material; the amount of PVA added to the B layer material is 10-15% of the weight of the B layer material.
7. The method for preparing the bismuth ferrite-barium titanate piezoelectric ceramic with a heterostructure according to claim 5, characterized in that: In step 5), the temperature of the silver-sintered plain sheet is slowly increased to 600° C. at a heating rate of 5° C. / min and kept at this temperature for 2 h.
8. The method for preparing the bismuth ferrite-barium titanate piezoelectric ceramic with a heterostructure according to claim 5, characterized in that: In step 5), the polarization electric field is 4000-5000 V / mm, the temperature is 80-100° C., and the time is 15-20 min.
Citation Information
Patent Citations
Sodium bismuth titanate base and barium titanate base multilayer composite piezoelectric film and making method thereof
CN104045340A
Varistor material and preparation method thereof
CN104725040A
High-temperature piezoelectric ceramic heterojunction material and preparation method thereof
CN116063072A
Liquid injection head, liquid injection apparatus, and piezoelectric element
JP2013120909A
Piezoelectric device, liquid-ejecting head, and liquid-ejecting apparatus
US20120200643A1